The Use of Hadith in Faḍāil A‘māl book - Alfi Syahriyati (JOURNAL OF QUR'AN AND HADITH STUDIES, 2018)
This paper aims to discuss the Hadith in the book of Faḍāil A'māl by Maulana Zakariyya al-Kandahlawi. This book is the primary reference for the Tablighi Jamaat group in practicing the sunnahs of the Prophet Muhammad pbuh. By adopting the al-Irāqi method in capturing the book  (takhrīj al-kitāb) of Iḥyā ‘Ulūm al-Dīn, this paper traces the authenticity of the Hadiths and potrays the interaction of the Tablighi Jamaat group with the book which later became a tradition in daily life. This paper find that there are 22 authentic (Ṣaḥiḥ) Hadiths, 1 good (Ḥasan) Hadith, 9 weak (dā’if) Hadith, 5 very weak (da’īf jiddan) Hadith, 1 fabricated (maudu’) Hadith, and 2 la aṣla lahu (lam ajidhu) Hadith in Faḍāil A'māl Book.